Penurunan Zat Organik dan Kekeruhan Menggunakan Teknologi Membran Ultrafiltrasi dengan Sistem Aliran Dead-End (Studi Kasus : Waduk Saguling, Padalarang) - Suprihanto Notodarmojo; Anne Deniva (Institute for Research and Community Services (LPPM) ITB, 2004)
A laboratory scale experiment to study the aplicability of ultrafiltration membrane technology to treat the water of Saguling Reservoir has been done. The main parameters in this study are flux, organic content, and turbidity. The membranes used are cellulose accetate based membrane, composed of 11, 13, 15 percent cellulose accetate respectively. Chemical analysis of Saguling Reservoir water shows that, color, organic content, and turbidity are the parameters exceeding the standard. In this study, treated water by using Poly Alummunium Chloride (PAC) as feeding solution was also been used. The results shows that CA-15, membrane has 15 % content of cellulose accetate, performed best. The permeability of the membrane was 5-12 l/m2.hr.bar, and rejects up to 90 % of organic content, 90-100% rejection of Total Suspended Solid and 90% turbidity.